The predictor factor of final visual acuity (VA) of acute retrobulbar neuritis patients receiving optic neuritis treatment trial (ONTT) regiment - Tatang Talka Gani; Melvina Nidya Sandra; Indra Tri Mahayana; Datu Respatika; Hartono Hartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
The study aimed to investigate the efficacy of intravenous optic neuritis treatment trial (ONTT) regiment on the treatment ofpatients with acute retrobulbar neuritis.This was a cross sectional studyusing medical records data of patients diagnosed with unilateral or bilateral retrobulbar neuritis by normal funduscopic findings and typical optic neuritis perimetry results within 14 days of onset fromtheNeuro-ophthalmology Clinic, Department of Ophthalmology, Dr. Sardjito General Hospital, Yogyakarta from January to December 2015. Medical records data of patients who received 1000 mg methylprednisolone IV per day for 3 days followed by 11 days 1 mg/kg body weight oral prednisolone were reviewed. Visual acuity (VA) at onset, final VA at time of follow up, delta VA improvement and time of follow up were included in the analyses.Twenty data of patients aged 33.95±8.07 years with VA at onset of 1.96±0.81 ( 1 mCF) were analyzed in this study. Significantly improvement in final VAafter treatment to be 1.39±1.12 ( 5mCF) was reported (p=0.001). The VA at onsetwas a predictive factor for final VA (p <0.001). Every 1.17 increase of final VA for every one-point decreased VA at onset (p<0.001). Time follow up showed to be trend (p=0.059),however, age and sex were not a predictive factorof final VA (p>0.05). In conclusion, there is VA improvement after the treatment of ONTT regiment. The VA at onset is a predictive factorof final VA on patients with acute retrobulbar neuritis.ABSTRAKPenelitian ini bertujuan mengkaji efektivitas regimen optic neuritis treatment trial (ONTT) intravena pada pengobatan pasien dengan neuritis retrobulbar faseakut. Penelitian potong lintang ini menggunakan rekam medis pasien yang didiagnosis neuritis retrobulbar unilateral atau bilateral dengan temuan funduskopi normal dan hasil perimetri neuritis optik yang khas dalam waktu 14 haris etelah onset dari Klinik Neuro-optamalmologi, Departemen Oftalmologi, Rumah Sakit Umum Pusat Dr. Sardjito, Yogyakarta dari Januari-Desember 2015. Data rekam medis pasien yang menerima1000 mg metilprednisolon IV per haris elama 3 hari diikuti oleh prednisolon oral selama 11 hari dengan dosis 1 mg/kg berat badan dianalisis. Ketajaman visual (VA) saat onset, VA akhir saat tindaklanjut, peningkatan VA, dan waktu tindak lanjut dianalisis. Sebanyak 20 data pasien berumur 33,95 ±8,07 tahun dengan VA saat onset 1,96 ±0,81 ( 1 mCF) dianalisis dalam penelitian ini. Perbaikan VA akhir menjadi 1,39±1,12 ( 5mCF) dilaporkan (p=0,001). Ketajaman visual saat onset merupakan factor predictor VA akhir (p<0,001). Setiap peningkatan VA akhir sebesar 1,17 menurunkan satu poin VA saat onset (p<0.001). Waktu tindak lanjut cenderung menjadi factor prediktor (p=0,059), namun demikian usia, jenis kelamin bukan factor predictor VA akhir (p>0,05). Dapat disimpulkan, terdapat peningkatan VA pasien setelah pengobatan regimen ONTT. Ketajaman visual saat onset merupakan factor prediktor VA akhir pada pasien dengan neuritis retrobulbar akut.